KEDUDUKAN ADILLAH ISTI’NASIYYAH DALAM PENGUATAN HUKUM FIKIH NORMATIF - Fathan Jihadul Islam; Akhmad Husaini; Deni Irawan (Sekolah Tinggi Dirasat Islamiyah Imam Syafi'i Jember, 2022)
In Islamic jurisprudence issues, sometimes problems are found for which there are no valid, clear, and firm evidences, whether from the agreed upon evidence or not. There is also issue that has evidences but there are other things that also strengthen the basis. This is not in the context of arguing, but is sometimes used to further solidify the outlook and action. The evidence is called adillah isti’nasiyyah. There are eleven adillah isti’nasiyyah found in this discussion. Two of them deserve to be promoted to adillah mukhtalaf fihi status. The two which went up in status were al-akhzu bi aqalli maqiila and al-istiqra’. The others are al-akhzu bil akhaff, al-akhzu bil aktsar, al-akhzu bil asyaq, al-akhzu bil wasth, dalalatus siyaq, dalalatul iqtiran, weak but has authentic eaning hadiths, al-ihtiyat, al-ilham. Discussions about the adillah isti’nasiyyah separately and comprehensively have not been found and discussed, although they still exist. Of course, it is necessary to elaborate further on this issue in order to add to the body of scientific knowledge. In discussing an Islamic jurisprudence issue, etc., scholars sometimes use this term in order to increase the basis for argumentation, even though in essence the evidences presented are sufficient.